2016
DOI: 10.1186/s12889-016-3664-y
|View full text |Cite
|
Sign up to set email alerts
|

The health and wellbeing of Australian farmers: a longitudinal cohort study

Abstract: BackgroundIsolation, long work days, climate change and globalization are just some of the many pressures that make farming a vulnerable occupation for incurring mental health issues. The objective of this study was to determine whether farming in Australia is associated with poorer wellbeing, physical and mental health, and less health service use.MethodsThe Australian Rural Mental Health Study, a longitudinal cohort study was analysed over four time points comparing farmers with non-farming workers (n = 1184… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
124
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 41 publications
1
124
0
3
Order By: Relevance
“…Talking about urban-rural differences, it is worth noting that, naturally, in rural areas there are longer distances between objects, including important institutions. Thus, remoteness is perceived as a factor lowering quality of life [164], because it can limit access to different institutions. However, in our research, a rise in distance from a set of institutions was correlated with a rise in the latent variable living conditions, which in consequence improved the mental comfort variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Talking about urban-rural differences, it is worth noting that, naturally, in rural areas there are longer distances between objects, including important institutions. Thus, remoteness is perceived as a factor lowering quality of life [164], because it can limit access to different institutions. However, in our research, a rise in distance from a set of institutions was correlated with a rise in the latent variable living conditions, which in consequence improved the mental comfort variable.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the good current economic situation is usually burdened with sacrifices in personal life. On the other hand, scholars have underlined that the bad economic situation of farmers, combined with other stress-generating factors (such as fluctuating weather, long work hours, lack of information, isolation, remoteness) result in the low level of farmers' mental comfort [164,168,169].…”
Section: Discussionmentioning
confidence: 99%
“…Remote farmers self-reported worse mental health and wellbeing than remote non-farm workers regardless of recent adverse life events, financial hardship or climatic adversity. 41 This compared to regional farmers, who did not differ from regional non-farm workers on either indice. 41 Geographical isolation, combined with loneliness, withdrawal and the intrinsic isolation of farming as an occupation 3,23 as well as sociocultural norms and attitudes 28,40,41 may therefore be relevant to increased rates of farmer suicide.…”
Section: Property Valuesmentioning
confidence: 85%
“…The need for control and self-reliance has been reported as a stronger barrier for farmers than non-farmers in seeking support for mental health problems in the same state. 40 In NSW, Brew et al (2016) 41 reported that all farmers, regardless of rurality, were half as likely to visit a GP or mental health professional in the last 12 months compared to non-farm workers, but that remote farmers were more likely to be more isolated and have less access (structural barriers) to care. Farmers are more than three times as likely to die by suicide in QLD than in NSW.…”
Section: Property Valuesmentioning
confidence: 99%
See 1 more Smart Citation